PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYWAN PT ASIAN TEC INDONESIA JAKARTA UTARA - Muhammad Firizki Arief; Nuridin; Diajeng Reztrianti (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2021)
To determine the effect of compensation and motivation on employee performance PT Asian Tec Indonesia North Jakarta. This research is included in the category of causal associative research using a quantitative approach. The research was conducted by distributing questionnaires to 30 respondents, all of whom were employees of PT Asian Tec Indonesia, North Jakarta, while the research method used partially and simultaneous linear regression analysis. The hypothesis states that partially compensation and motivation have a positive effect on employee performance. The hypothesis which states that compensation and motivation simultaneous have an effect on employee performance.